2014
DOI: 10.1002/rcm.7001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid profiling and structural characterization of bioactive compounds and their distribution in different parts ofBerberis petiolarisWall. ex G. Don applying hyphenated mass spectrometric techniques

Abstract: Rapid and accurate HPLC/ESI-QTOF-MS/MS and UPLC/ESI-QqLIT-MS/MS methods were established for identification, characterization and quantification of phytochemicals in the ethanolic extract of Berberis petiolaris. These methods, therefore, can be used for studies on phytochemical variation in different parts of the plant. Principle components analysis (PCA) may be used for plant part discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Compound at peak 12 corresponded to oblongine ( m/z 314.1752), produced the RDA fragment ion having a formula [C 3 H 8 N] + from the loss of [(CH 3 ) 2 N = CH 2 ] + group thereby showing the presence of two methyl groups on the nitrogen. The benzyl fragment ion and isoquinoline fragment ion supported the presence of methoxyl and hydroxyl groups in the isoquinoline moiety (Nikolic et al, ; Singh et al, ) as shown in Scheme S4 (in the on‐line Supporting information).…”
Section: Resultsmentioning
confidence: 78%
“…Compound at peak 12 corresponded to oblongine ( m/z 314.1752), produced the RDA fragment ion having a formula [C 3 H 8 N] + from the loss of [(CH 3 ) 2 N = CH 2 ] + group thereby showing the presence of two methyl groups on the nitrogen. The benzyl fragment ion and isoquinoline fragment ion supported the presence of methoxyl and hydroxyl groups in the isoquinoline moiety (Nikolic et al, ; Singh et al, ) as shown in Scheme S4 (in the on‐line Supporting information).…”
Section: Resultsmentioning
confidence: 78%
“…For compounds 3 and 8 , the ions [M–NH(CH 3 ) 2 ] + and [CH 2 = N (CH 3 ) 2 ] + ( m/z 58.066) suggested the presence of two methyl groups on the nitrogen. The isoquinoline fragment at m/z 192.10, the benzyl fragment at m/z 107.048 and other diagnostic ions at m/z 237.089, 175.074 and 143.048 were consistent with those of oblongine, which has been reported in Stephania cepharantha (Tanahashi et al , ; Singh et al , ). Compounds 3 and 8 were therefore tentatively identified as oblongine with a hexose and oblongine, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Aporphine alkaloids produce [M] + or [M + H] + ions, and their MS/MS fragmentation is generally initiated by loss of the amino group and its substituent. Further fragmentations involve losses of CH 3 , CH 3 O, CH 2 O, CH 3 OH and CO (Stévigny et al , ; Jeong et al , ; Singh et al , ; Sim et al , ). According to the mass spectrum patterns, compounds 9 , 14 , 25 , 29 , 31 and 37 were deduced as aporphine alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…According to the data in the literature, benzyl fragment, as the most intense fragment ions, show in benzylisoquinoline alkaloids without a functional group at C‐11 due to their lesser ability to stabilise the benzyl leaving group. While benzylisoquinolines have less rigid structures, the small fragments below m/z 150 can generally be formed by the cleavage of the alkaloid skeleton and successive losses of peripheral groups, which provide important information about the substitution on rings A and C …”
Section: Resultsmentioning
confidence: 99%